Karakteristik Objek Wisata di Kecamatan Tatapaan Kabupaten Minahasa Selatan - Darotong, Vivilia Fitri; Tendean, Maxi; Andaria, Kalvin Salindeho; Kaihatu, Jolanda Esther (Jurnal Social Science, 2024)
This research focuses on the type of tourist attraction, the attractiveness of the tourist attraction, and the development of tourism potential. The method used is descriptive qualitative. The research results show that there are potential tourist attractions consisting of 1) Mangrove forest area, 2) Pasir Putih Beach, 3) Shoe Island, 4) Wawontulap Beach Resort Beach, 5) Popareng Beach, 6) Amurang Bay, 7) Bonar Doa Hill, and 8) Rap-rap Waterfall. Tourist attractions are natural beauty, beautiful and shady forests, and friendly residents. Development efforts carried out include, 1) planning the arrangement of tourist attraction areas, 2) carrying out repairs and construction of road facilities, 3) providing facilities and infrastructure as tourist attraction facilities, and 4) carrying out community empowerment activities.